2008
DOI: 10.1177/1089313x0801200402
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Turnout in Dance Research: A Critical Review

Abstract: Turnout measurement procedures, results, and reporting formats vary in dance medicine and science research, making comparisons difficult. It is agreed that turnout results from summative contributions of the hip, knee, lower-leg, and the foot-ankle complex. However, the most frequently reported measurement is hip external rotation, and even this is measured in incompatible ways. No normative data exist for component and summative measures or for different categories of dancers, making screening, clinical asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The turnout angle for the functional turnout position was at which each participant could make a turnout without floor friction. Referring to a previous study, the participants were instructed to create a maximum hip joint external rotation in a supine position with an extended hip and knee joint 25 . The physical therapist as an examiner measured the angle between the second toes on each side with respect to the center of the heels of their feet using a goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…The turnout angle for the functional turnout position was at which each participant could make a turnout without floor friction. Referring to a previous study, the participants were instructed to create a maximum hip joint external rotation in a supine position with an extended hip and knee joint 25 . The physical therapist as an examiner measured the angle between the second toes on each side with respect to the center of the heels of their feet using a goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…28 It has been suggested that 50% to 70% of turnout should come from the hip in order to reduce excessive tibial torsion stress on the knee. 30,31 Percentiles for active standing turnout for all participants ranged between 121.1 and 131.0° across all groups. This is consistent with finding in other pre-professional ballet cohorts with an average active standing turnout of 123.4° and a little less than professional classical ballet dancers (133.0° ).…”
Section: Active Standing Turnoutmentioning
confidence: 97%
“…The turnout angle for the functional turnout position was at which each participant could make a turnout without oor friction. Referring to a previous study, the participants were instructed to create a maximum hip joint external rotation in a supine position with an extended hip and knee joint [27]. The physical therapist as an examiner measured the angle between the second toes on each side with respect to the center of the heels of their feet using a goniometer.…”
Section: Experimental Tasksmentioning
confidence: 99%